2017
DOI: 10.3389/fpsyt.2017.00089
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effects of a Novel Benzofuranyl-Piperazine Serotonin-2C Receptor Agonist Suggest a Potential Therapeutic Application in the Treatment of Obsessive–Compulsive Disorder

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are the only effective pharmacological treatments for obsessive–compulsive disorder (OCD). Nonetheless, their generally limited efficacy, side-effects, and delayed onset of action require improved medications for this highly prevalent disorder. Preclinical and clinical findings have suggested serotonin2C (5-HT2C) receptors as a potential drug target. Data in rats and mice are presented here on the effects of a novel 5-HT2C receptor agonist ((3S)-3-Methyl-1-[4-(tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(33 reference statements)
1
6
0
1
Order By: Relevance
“…Thus, HD and LD rats selected by SIP has shown consistent behavioral differences among different behavioral paradigms. Otherwise, SIP is considered a good model for researching the psychopharmacology of the compulsive phenotype (Platt et al, 2008; Moreno and Flores, 2012; Rodriguez et al, 2017). Indeed, studies on SIP revealed the efficacy of antipsychotic (haloperidol, clozapine, and pimozide) and antidepressant (fluoxetine) drugs in reducing SIP water intake (Snodgrass and Allen, 1989; Didriksen et al, 1993; Mittleman et al, 1994; Hogg and Dalvi, 2004; Dwyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HD and LD rats selected by SIP has shown consistent behavioral differences among different behavioral paradigms. Otherwise, SIP is considered a good model for researching the psychopharmacology of the compulsive phenotype (Platt et al, 2008; Moreno and Flores, 2012; Rodriguez et al, 2017). Indeed, studies on SIP revealed the efficacy of antipsychotic (haloperidol, clozapine, and pimozide) and antidepressant (fluoxetine) drugs in reducing SIP water intake (Snodgrass and Allen, 1989; Didriksen et al, 1993; Mittleman et al, 1994; Hogg and Dalvi, 2004; Dwyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One of those models (schedule-induced polydipsia in rats) relies on performance of consummatory behaviors, whereas the other two (marble burying and nestlet shredding in mice) depend on performance of nonconsummatory behaviors that are repetitive and nonhabituating. Both CPD 1 and fluoxetine suppressed marble burying and nestlet shredding, with CPD 1 dose-dependently decreasing excessive drinking engendered by a schedule of intermittent food delivery (schedule-induced polydipsia) (Rodriguez et al, 2017). The researchers concluded that the behavioral specificity of effects of CPD 1 against repetitive and excessive behaviors suggests a potential therapeutic application in OCD, thus supportive of the therapeutic utility of stimulating 5-HT2C receptors in OCD.…”
Section: A Probing the Role Of Neurotransmitters In Obsessive-compulsive Disordermentioning
confidence: 96%
“…A recent study (Rodriguez et al, 2017) considered the effects of a novel 5-HT2C receptor agonist, (3S)-3methyl-1-[4-(trifluoromethyl)-7-benzofuranyl]-piperazine (CPD 1), with high potency and full efficacy at 5-HT2C receptors in three animal model preparation of OCD. One of those models (schedule-induced polydipsia in rats) relies on performance of consummatory behaviors, whereas the other two (marble burying and nestlet shredding in mice) depend on performance of nonconsummatory behaviors that are repetitive and nonhabituating.…”
Section: A Probing the Role Of Neurotransmitters In Obsessive-compulsive Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…In SIP-prone rats, differences in the binding affinity of DA D1-like/D2-like receptors exist in limbic and cortical circuits (amygdala, VTA, NAc, and medial prefrontal cortex [mPFC]) (Pellón et al, 2011). Furthermore, pharmacological pretreatment with either DA agonists/antagonists, serotonergic or monoamine modulators, reduce SIP behaviors (i.e., drinking and licking; see Table 2) (Moreno and Flores, 2012; Navarro et al, 2015; Rodriguez et al, 2017; Sukhanov et al, 2019). High drinking rats also show elevated serotonergic activity in the amygdala (Moreno et al, 2012) and reduced 5-HT 2A receptor binding in the mPFC (Mora et al, 2018) with additional evidence for changes in DA activity in the PFC, NAc, and amygdala (Moreno et al, 2012).…”
Section: Schedule-induced Polydipsia As a Model Of Obsessive Compulsimentioning
confidence: 99%